A High-Order Discontinuous Galerkin Method for the Two-Dimensional Time-Domain Maxwell's Equations on Curved Mesh (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, a DG (Discontinuous Galerkin) method which has been widelyemployed in CFD (Computational Fluid Dynamics) is used to solve the two-dimensionaltime-domain Maxwell's equations for complex geometries on unstructuredmesh. The element interfaces on solid boundary are treated in both curved wayand straight way. Numerical tests are performed for both benchmark problems andcomplex cases with varying orders on a series of grids, where the high-order convergencein accuracy can be observed. Both the curved and the straight solid boundaryimplementation can give accurate RCS (Radar Cross-Section) results with sufficientlysmall mesh size, but the curved solid boundary implementation can significantlyimprove the accuracy when using relatively large mesh size. More importantly, thisCFD-based high-order DG method for the Maxwell's equations is very suitable forcomplex geometries.